The Influence of Human Resource Competency and Government Internal Control System on the Quality of Regional Asset Management with Organizational Commitment as a Moderating Variable (Survey on Regional Work Units of West Java Province) - Nur Azizah, Mitha; Hendaris, R. Budi (Dinasti Publisher, 2025)
The purpose of this study is to investigate the influence of human resource competency and the government’s internal control system on regional asset management quality within the West Java Provincial Government. The context of this research is based on the Report on the Examination Results of the Internal Control System and Compliance of the West Java Provincial Government for 2023, which states that the fixed asset management within the West Java Provincial Government is still inadequate due to over and under-recording of fixed asset values. This research uses a sample of 76 respondents taken from all Regional Work Units within the West Java Provincial Government. The testing was conducted using the SEM PLS method with the assistance of the SmartPLS 4 application. The study reveals that the quality of local asset management is significantly and favorably impacted by the internal control system and competency of human resources partially. However, the findings revealed that organizational commitment did not moderate the relationship between the quality of local asset management and either the government's internal control system or human resource competency.